2018
DOI: 10.3329/bjms.v17i1.35275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation on red blood cells at different storage period: A comparative study

Abstract: Objectives: The objective of this study was to explore the effect of gamma irradiation on the haematological and biochemical parameters of the allogeneic red blood cells units at different storage duration. Methods: A prospective comparative study was conducted at the Blood Bank unit, Department of Diagnostic Laboratory Services of Universiti Kebangsaan Malaysia Medical Centre (UKMMC) in year 2013. Total 36 allogeneic red blood cell units were selected by simple random sampling method and divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…La bomba de Na + /K + desempeña un papel muy importante en el mantenimiento del volumen celular, iguala la presión osmótica a ambos lados de la membrana y mantiene el potencial de membrana. Se ha visto, además, que la irradiación promueve la generación de especies reactivas del oxígeno y la peroxidación de lípidos de la membrana de los glóbulos rojos [3], incrementa la ©2024 Anales AFA permeabilidad de la membrana eritrocitaria al potasio, sodio y hemoglobina, y disminuye su deformabilidad [4][5][6][7][8]. Todos estos efectos sobre los glóbulos rojos reducen la viabilidad transfusional de las unidades irradiadas almacenadas disminuyendo su viabilidad de 42 a 28 días [9].…”
Section: Introductionunclassified
“…La bomba de Na + /K + desempeña un papel muy importante en el mantenimiento del volumen celular, iguala la presión osmótica a ambos lados de la membrana y mantiene el potencial de membrana. Se ha visto, además, que la irradiación promueve la generación de especies reactivas del oxígeno y la peroxidación de lípidos de la membrana de los glóbulos rojos [3], incrementa la ©2024 Anales AFA permeabilidad de la membrana eritrocitaria al potasio, sodio y hemoglobina, y disminuye su deformabilidad [4][5][6][7][8]. Todos estos efectos sobre los glóbulos rojos reducen la viabilidad transfusional de las unidades irradiadas almacenadas disminuyendo su viabilidad de 42 a 28 días [9].…”
Section: Introductionunclassified
“…In previous works, the biochemical and hematological effects of gamma irradiation at different storage periods were studied. It was observed that irradiation of the erythrocytes increases red cells hemolysis and leakage of intracellular potassium (Adams, F. et al, 2015;Yousuf, R. et al, 2018). The mechanisms through which irradiation causes the loss of RBC viability could be related to the primary effects of radiation.…”
Section: Introductionmentioning
confidence: 99%